Improving Students’ Achievement in Narrative Writing Through Experiential learning - Amalia Novita Sari; Masitowarni Siregar (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study dealt with the improvement of students’ narrative writing achievement through Experiential Learning. The objective of this study was to find out whether students’ achievement in narrative writing can be improved if the students are taught by using Experiential Learning technique. This study was conducted by using classroom action research. The subject of this study was class XI IA-1 of SMA Negeri 4 Pematangsiantar, consisted of 36 students. The research was conducted in two cycles; each cycle consisted of three meetings. The instruments of data collections were writing tests for the quantitative data, and observation sheets and diary notes for the qualitative data. By the end of Cycle II there was an improvement as much as 25.56 points in the mean of the students’ score or 50.7% higher than the preliminary test. The research findings proved that Experiential Learning can significantly improve students’ achievement in narrative writing.   Keywords: Narrative Writing, Experiential Learning, Students’ Achievement